PENGARUH NILAI TUKAR, PENANAMAN MODAL DALAM NEGERI (PMDN), DAN PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Dessy Triaz Wulandari; Aris Soelistyo; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2020)
Economic growth is a matter of the economy in the long term and influenced by various factors in carrying out economic development. This study aimed to analyze the exchange rate, domestic investment, and government spending in the education sector on economic growth in Indonesia. The analytical method used in this research was the Multiple Linear Regression technique. For the purpose of analysis used secondary data from the 1999-2018 time series are used, namely Indonesian GDP data, exchange rate data, the value of domestic investment realization, and education sector government expenditure data. The data source of this research came from the official website of the Indonesian Statistics Agency, and sources from the research journal. The results showed the variables of exchange rates, domestic investment, and government spending in the education sector simultaneously and partially had a positive and significant impact on economic growth in Indonesia by the coefficient value of 0.0068, 0.0068 and 0.0000.